Migrants and Refugees: Different Approaches in Local Communities and Impacts on Public Safety in Bosnia and Herzegovina - Šabanija, Senadin (Kriminalističke teme, 2022)
A negative impact on public safety and security caused by the massive presence of different categories of migrants and refugees in Bosnia and Herzegovina is considered a source of instability for the last several years. Current migration management approaches in Bosnia and Herzegovina seem to be ineffective and causing direct impacts on security in local communities. Frequent violations of basic human rights and freedoms of migrants often causing adverse responses against public safety in local communities. Securitization of migrations in Bosnia and Herzegovina becomes a legitimate approach by different organizational levels and further leading to the humanitarian crisis of unprecedented scale. It is necessary to change the current approach in Bosnia and Herzegovina to improve the migration management process in local communities ensuring minimal impacts on public safety and security. The unified, organized, and effective approach in establishing migrant transit centers based on humanitarian principles might bring many benefits to local communities. Overall positive effects of such solution might abolish any financial constraint argued by local authorities in Bosnia and Herzegovina. Comparative analysis of different migrations strategies implemented in Turkey and Greece suggests that the migration crisis approach should be highly coordinated and, to a certain level, centralized to prevent negative implications on public security.